The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1161/strokeaha.110.581512
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of High-Density Lipoprotein-Based Therapy in a Model of Embolic Stroke

Abstract: Background and Purpose-High-density lipoprotein (HDL) levels are inversely associated with stroke incidence, suggesting a protective effect. Using a rat model, we tested the hypothesis that HDL exerts direct vasculo-/ neuroprotective effects when administered during the acute phase of embolic stroke. Methods-After embolic occlusion, Sprague-Dawley rats were randomly treated intravenously with purified HDL versus saline immediately (2, 10 mg/kg) or 3 or 5 hours (10 mg/kg) after stroke. The effects of HDL were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
(30 reference statements)
3
48
1
Order By: Relevance
“…Second, we observed that treatment of DOCA-salt or Ang II hypertensive mice with the ApoA1 mimetic peptide 4F largely prevents the blood cell recruitment responses normally elicited in untreated WT mice. These findings are consistent with reports describing an antiinflammatory action of HDL cholesterol, [31][32][33] genetic overexpression of ApoA1 34,35 as well as 4F treatment. 36,37 The antiinflammatory effects of HDL and ApoA1 have been attributed to an attenuation of leukocyte activation 38 and endothelial cell adhesion molecule expression, 39 possibly resulting from enhanced nitric oxide production.…”
Section: Discussionsupporting
confidence: 93%
“…Second, we observed that treatment of DOCA-salt or Ang II hypertensive mice with the ApoA1 mimetic peptide 4F largely prevents the blood cell recruitment responses normally elicited in untreated WT mice. These findings are consistent with reports describing an antiinflammatory action of HDL cholesterol, [31][32][33] genetic overexpression of ApoA1 34,35 as well as 4F treatment. 36,37 The antiinflammatory effects of HDL and ApoA1 have been attributed to an attenuation of leukocyte activation 38 and endothelial cell adhesion molecule expression, 39 possibly resulting from enhanced nitric oxide production.…”
Section: Discussionsupporting
confidence: 93%
“…Planimetric measurements (Image J software, National Institutes of Health, Bethesda, MD) were performed blinded to the treatment group and were used to calculate infarct volumes and brain edema. 26 The occurrence of hemorrhagic transformation (HT) was macroscopically assessed on whole brains and again after the 2-mm thick coronal brain slices were cut before 2,3,5-triphenyltetrazolium chloride staining.…”
Section: Determination Of Infarct Size Brain Edema and Hemorrhagic mentioning
confidence: 99%
“…26 Neurological function was graded on a scale of 0 to 10 ( Figure II in the online-only Data Supplement). Neurological Severity Score was assessed immediately before euthanization at 24 hours after stroke onset.…”
Section: Neurological Deficit Evaluationmentioning
confidence: 99%
“…They showed that high doses of rHDLs (120 mg/kg) infused 2 h before the onset of stroke reduced the brain necrotic area by 61 and 76 %, respectively, in an excitotoxic (NMDA) and a transient MCAO model of stroke in rats. More recently, we have shown that plasma HDLs (10 mg/kg), injected immediately or at 3 or 5 h after stroke, also reduced cerebral infarct volume by 74, 68 and 70 %, respectively, in a rat model of thromboembolic stroke (Lapergue et al 2010). This was associated with a reduced BBB breakdown and decreased neutrophil recruitment in the infarct area.…”
Section: Hdls and Acute Stroke: Experimental Modelsmentioning
confidence: 82%
“…In rat type I astrocytes and glioma cells, HDLs stimulated DNA synthesis and expression of fibroblast growth factor-2, a potent neurotrophic factor, which was associated with the activation of proliferative intracellular signalling (Malchinkhuu et al 2003). It is likely that in pathological conditions (haemorrhage or transient increase of BBB permeability), HDLs have an improved access to the cerebral parenchymal compartment and then act on both neurons and astrocytes (Lapergue et al 2010 Under acute stroke conditions, the lipid profile has been reported to be modified (Santos-Silva et al 2002). These authors have shown that patients with diagnosed ischaemic stroke (CT imaging, n ¼ 21) had lower plasma concentrations of both HDL and apo A-I than healthy subjects with no history of cardiovascular events and normal haematologic values (n ¼ 29).…”
Section: Lipoproteins In the Brainmentioning
confidence: 99%